ANALISYS OF CULTURAL TOURISM POTENTIAL OF NAGARI SIJUNJUNG TRADITIONAL VILLAGE, SIJUNJUNG DISTRICT - Sri Delvi Oktavia; Sri Mariya (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The aim of this research is to find out cultural tourism attractions and the tourism potential in the Nagari Sijunjung Traditional Village, Sijunjung Regency. Using descriptive qualitative research methods, research information was obtained using purposive sampling techniques. In collecting data, using interview anda observation techniques. The research results obtained are that Nagari Sijunjung Traditional Village is a picture of the life of the matrilineal Minangkabau community. An exotic village with stretches of gadang houses, local wisdom that is still preserved and still strong in its customs, people who still carry out traditional proscessions such as the Bakaua Adat, Mambantai Adat, the Traditional Marriage Procession, Tobo Kongsi dan Batagak Gala. Various strains of traditional arts and culinary arts as well as matrilineal festival enrich the cultural tourism potential in this Traditional Village. Cultural tourism in the Nagari Sijunjung Traditional Village is also supported by accessibility and adequate facilities and infrastructure to support tourism activities.